10Be surface exposure dating reveals unexpected high deformation rates in the central Andean wedge interior. (30th July 2020) - García Morabito, Ezequiel; Terrizzano, Carla M.; Zech, Roland; Yamin, Marcela; Wüthrich, Lorenz; Christl, Marcus; Ramos, Víctor A.; Haghipour, Negar; Cortés, José M.
Abstract: Understanding deformation associated with active thrust wedges is essential to evaluate seismic hazards. In this study, we investigate the spatial distribution, timing, and rates of deformation across the central Andean backarc of Argentina, where deformation and shortening have been assumed to occur within a narrow wedge‐front zone. The combined results of our geomorphic mapping, topographic surveying, and 10 Be exposure dating demonstrate that fault activity related to the growth of the Andean orogenic wedge is not only limited to a narrow thrust front zone but also occurs in the Andean wedge interior. There, internal structures with deformation rates of ca. 1.3 mm/year have been active during the last ~140 ka. Widely distributed deformation implies that seismic hazards may have been underestimated in the internal part of the Andean orogen.